The oxford handbook of state and local government - Haider-Markel, Donald P, Ed (The Oxford handbooks of American politics, 2014)
This book is an historic undertaking. It contains a wide range of essays that define the important questions in the field, evaluate where we are in answering them, and set the direction and terms of discourse for future work. The 'Handbook' will have a substantial influence in defining the field for years to come. The chapters critically assess both the key works of state and local politics literature and the ways in which the sub-field has developed. It covers the main areas of study in subnational politics by exploring the central contributions to the comparative study of institutions, behavior, and policy in the American context. Each chapter outlines an agenda for future research.